Life table and demographic parameters of helopeltis theivora waterhouse (Hemiptera: miridae) - Paul, Shovon Kumar; Adam, Nur Azura; Jamian, Syari; Mokhtar, Anis Syahirah (Editorial board of Journal of Experimental Biology and Agricultural Sciences, 2025)
Helopeltis theivora is a significant pest of tea, causing economic losses through direct feeding damage to tender shoots in various tea-growing regions of Asia, including Malaysia. Understanding the population dynamics of this pest through life table analysis and demographic parameters is essential for identifying critical stages in its life cycle that influence population growth. Therefore, this study aimed to construct life tables and demographic parameters to assess the population dynamics of H. theivora on tea shoots. The experiment was conducted under controlled laboratory conditions at a temperature of 25 ± 1°C, a relative humidity of 70 ± 5%, and a 12:12 h light-dark photoperiod, using three cohorts of H. theivora, each consisting of 103, 105, and 113 one-day-old eggs. Observations were recorded daily on survival, mortality, and fecundity for each cohort to construct age-specific life tables and determine key demographic parameters. The life table analysis revealed that H. theivora exhibited a Type III survivorship curve, characterized by high mortality during the early developmental stages. The first instar nymphs experienced the highest mortality rate (22.47%), corresponding to a K-value of 0.111, indicating that this stage is crucial for managing the H. theivora population. Life expectancy (ex) for H. theivora decreased gradually as the individuals grew and developed. Overall, 40.81% of individuals reached adulthood, with a female-biased sex ratio of 1.0:0.92 (female to male). Female emergence began on day 23, while the last female died on day 69. Oviposition commenced on day 27 and continued until day 65, with a peak in egg-laying observed between days 34 and 45, accounting for 58.32% of the total egg production. On average, a female lived for 38.60 ± 1.60 days and laid approximately 160.47 ± 16.33 eggs during her lifetime. Demographic analysis revealed a high reproductive potential, with a net reproductive rate (R0) of 29.56 female offspring per female per generation, a mean generation time (Tc) of 38.68 days, an intrinsic rate of natural increase (rm) of 0.09 offspring per female per day, a finite rate of increase (λ) of 1.09 female offspring per female per day, and a population doubling time (DT) of 7.92 days. The results of this study indicate that management strategies should be implemented during the early nymphal stages, particularly during the first instar, to suppress the H. theivora population effectively.